Exercise intolerance and heart failure : role of vascular dynamics and impact of exercise interventions - Silva, Natália Turri da (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Agronomia e Medicina Veterinária, Programa de Pós-Graduação em Saúde Animal, 2022.